EFEKTIVITAS PEMBERIAN PROGRESSIVE MUSCLE RELAXATION DIBANDINGKAN AROMATHERAPY MASSAGE UNTUK MENINGKATKAN KUALITAS TIDUR PADA PEKERJA PEREMPUAN DI RUMAH SAKIT BALI ROYAL DENPASAR - Ni Made Nuari Diahputri; Anak Ayu Nyoman Trisna Narta Dewi; Luh Made Indah Sri Handari Adiputra (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2017)
ABSTRACT Sleeping quality is someone’s satisfaction about his or her sleeping to rest their body and mind in order to reduce fatigue. The Progressive Muscle Relaxation (PMR) and Aromatherapy Massage are some of the therapy relaxation used to improve the sleeping quality. The Wilcoxon Sign Rank Test showed significant results with p value=0,007 (p<0,05) in Progressive Muscle Relaxation (PMR) group and p value=0,006 (p<0,05) in Aromatherapy Massage group, that means there was significance difference of the increase of sleeping quality before and after intervention. The result of Mann-Whitney U-test revealed there was no difference on mean of sleeping quality score improvement between Progressive Muscle Relaxation (PMR) and Aromatherapy Massage group, with p value=0.738 (p>0.05). It can be concluded that Progressive Muscle Relaxation (PMR) is as good as Aromatherapy Massage in improving sleeping quality of women employees in Bali Royal Hospital Denpasar. Keyword: Sleeping quality, Progressive Muscle Relaxation, Aromatherapy Massage, Pittsburgh Sleep Quality Index Questioner.